P01.100 Tumour treating fields: Acceptable, tolerable, and can we reduce cost?. (19th September 2018) - Brodbelt, A; Williams, M; Thorpe, A; Mills, S; Price, S; Lekka, E; Watts, C; Davies, C; Jenkinson, M
Abstract: Background: Tumour treating fields (TTF) are a novel anticancer treatment that uses alternate electrical fields to disrupt cell division. In a randomized controlled trial, TTF significantly improved survival in patients with Glioblastoma. Use of the device is intensive for patients, with almost constant electrode application and battery use. Treatment currently costs €21, 000 per month. Methods were explored to reduce cost and to examine acceptance and tolerability in a social health care setting. Material and Methods: Three UK centres were offered support for trialing the treatment. Patients with proven MGMT unmethylated glioblastoma, had completed radical chemoradiotherapy, had a performance score >70, and had social support (for placing the electrodes), where approached. Monthly assessments of compliance and quality of life (QOL) (EORTC BT 20), and quarterly MRIs and tolerability questionnaires were completed. Reductions in company support were explored to reduce device costs. Results: Oncologists in one centre declined to support any use of the device, so no patients were approached in that centre. 8 patients were approached in the other two centres, 5 accepted, and 1 further patient had treatment started elsewhere. Company home visits were not offered and clinicians were trained in the use and interface with the equipment. All patients tolerated the treatment. The main reason for patient refusal was monthly travelling for compliance checks. The main adverse comments related to the weight of the mobile battery. Two patients had skin irritation, and two patients found that the only aspect of life affected was showering. Four patients have progressed, but maintained stable QOL scores. Two patients have since died. Conclusion: Tumour treating fields is a well tolerated but intensive treatment, and acceptable to a UK population. At present monthly company support on site is still required, but future improvements in software may allow further reductions in on site support leading to cost reduction. A significant reduction in cost is required to allow routine UK use in a social care setting.